Der europäische Haushalt bis 2020: Anspruch und Wirklichkeit - Michael Broer (Wirtschaftsdienst, 2013)
Die Europäische Union entwickelt sich immer stärker in Richtung einer zusätzlichen föderalen Ebene neben Bund, Ländern und Gemeinden. Ihre Aufgaben, Ausgaben und Einnahmen und somit der EU-Haushalt und der dazugehörige Mehrjährige Finanzrahmen sind für ihre Arbeit zentral. Derzeit wird für den Zeitraum bis 2020 der Kommissionsentwurf für den neuen Mehrjährigen Finanzrahmen politisch verhandelt. Bisherige Einigungsversuche sind gescheitert, da unter anderem die Zahler- und die Empfängerländer unterschiedliche Interessen verfolgen. – – The Commission of the European Union (EU) has made a new proposal regarding the multiannual financial framework through 2020. Raising expenditures with high added value for the EU (e.g. a trans-European transport network) is one important target of the proposal. Another important issue is a change to the fiscal system. The Commission intends to participate in the revenue of a new financial transaction tax. One problem of the proposal is the gap between desire and reality. A look at the structure of the expenditures through 2020 shows, like in the past, more than 40% of the budget is intended for the Common Agricultural Policy and not for European public goods or similar expenditures. This structure makes it unlikely to achieve high added value for the EU.
Keywords: H10; H77; H87; 330; EU-Finanzen; Politische Entscheidung; EU-Staaten